Francisco Levita, Negreiros-Dantas, Uma página para a história da literatura nacional. Óscar, Pereira São-Pedro (Pintor), Tristão de Teive, Príncipe de Judá, Coimbra Manifesto 1925 - Marnoto, Rita (2009)
(2009). Francisco Levita, Negreiros-Dantas, Uma página para a história da literatura nacional. Óscar, Pereira São-Pedro (Pintor), Tristão de Teive, Príncipe de Judá, Coimbra Manifesto 1925. Lisboa: Fenda [pp. 98]. ISBN 978 989 603 038 4 Direitos de autor